2020
DOI: 10.1186/s12870-020-02445-w
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin may increase disease resistance and flavonoid biosynthesis through effects on DNA methylation and gene expression in grape berries

Abstract: Background Melatonin can regulate plant growth, development and biotic responses by causing global changes in gene expression; however, the melatonin-induced changes in gene expression via the modification of DNA methylation remain unclear in plants. Results A total of 1,169,852 and 1,008,894 methylated cytosines (mCs) were identified in the control and melatonin-treated grape berries, respectively, and mCs occurred primarily at CG sites, followed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(34 citation statements)
references
References 46 publications
4
30
0
Order By: Relevance
“…3a, b and S3a–c ). These results agreed with those found in grape berries, which showed that exogenous melatonin treatment decreased the methylation levels of various gene regions in the CHG and CHH contexts 40 . It was reported that the DNA demethylase DML2 was downregulated under cold stress in tomato, which resulted in the hypermethylation of the promoter and silencing of genes involved in the biosynthesis of flavor volatiles 41 .…”
Section: Discussionsupporting
confidence: 91%
“…3a, b and S3a–c ). These results agreed with those found in grape berries, which showed that exogenous melatonin treatment decreased the methylation levels of various gene regions in the CHG and CHH contexts 40 . It was reported that the DNA demethylase DML2 was downregulated under cold stress in tomato, which resulted in the hypermethylation of the promoter and silencing of genes involved in the biosynthesis of flavor volatiles 41 .…”
Section: Discussionsupporting
confidence: 91%
“…7C, D ). Additionally, our recent study revealed that MT increased the expression of another STS gene by decreasing its promoter methylation 33 . Therefore, STSs may represent a key point in the pathway regarding the regulation of resveratrol by MT or MT via ethylene.…”
Section: Discussionmentioning
confidence: 93%
“…tritici ( Bgt ), the upregulation of a pathogenesis-related defense gene AeGlu is attributed to CHH hypomethylation in the promoter [ 147 ]. The increased transcription of ENHANCED DISEASE SUSCEPTIBILITY1 ( EDS1 ) in melatonin-treated grape ( Vitis vinifera ) berries with enhanced resistance to the necrotrophic fungus Botrytis cinerea ( B. cinerea ) also correlates with its decreased promoter methylation level [ 148 ].…”
Section: Chromatin Dynamics Associated With Biotic Stress-induced mentioning
confidence: 99%